Does metal transfer differ on retrieved Biolox® Delta composites femoral heads? Surface investigation on three Biolox® generations from a biotribological point of view. (15th March 2017) - Affatato, Saverio; Ruggiero, Alessandro; Merola, Massimiliano; Logozzo, Silvia
Abstract: Background: Currently, little is known about the effects that metal transfer affecting hip implants may have on roughness. The main aim of this study is to propose a metrological technique in order to better characterize this phenomenon on the surface of composite ceramic femoral heads, discussing its influence on the biotribological behaviour of the coupling. In addition, through the acquired data, we investigate whether the metal transfer extension and roughness alterations on a femoral head is correlated to the material, the follow-up of the implant and whether metal transfer is associated with changes in the roughness of alumina surface, considering different follow-ups . Methods: Three generations of femoral heads manufactured in ceramic (Biolox ®, Biolox ® Forte, and Biolox ® Delta) were retrieved from patients after different implantation periods (mean follow up = 6.9 years) and they were analysed using a roughness tester and an optical non-contact 3D scanner, in order to characterize the metal transfer on the bearing surface. Results: Surface area where the metal transfer was observed ranged between 29.6 mm 2 and 573.6 mm 2 . The mean values of Sa (average roughness) were different between the Affected Zone (0.3 ± 0.1 μm) and Unaffected Zone (0.03 ± 0.1 μm). In particular, regions of metal transfer were rougher than the non-metal transfer regions of the articular surface and this is demonstrated by both the areal roughness parameters considered: Sa (arithmetic mean height) and St (maximum height of the surface) parameters (p = 0.002, Wilcoxon paired-test). St parameter acquired on the Biolox ® Delta femoral heads showed the lowest mean value (11.92 μm). Conclusion: We found no correlation between follow-up vs . roughness and total surface area of metal transfer. Furthermore, we found that the amount of areal coverage of metal transfer is correlated with the surface roughness. Finally, MT effect on composite ceramic implants caused lower height of peaks and valleys when compared to common ceramic.